Signaling Dissent: Political Behavior in the Arab World - Raj M. Desai; Anders Olofsgård; Tarik Yousef (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2018)
What explains the variety of political behavior observed across the Arab world in recent years? We model political participation as a continuum from non-violent to violent activities where the chief purpose of political action is to signal discontent. The credibility of those signals, however, depends on the personal cost of political engagement, with the result being that individuals from both extreme high-cost and low-cost groups may self-exclude even when highly discontent. We show, further, that political violence constitutes a credible alternative for those for whom peaceful protest carries little signaling value. Using data from three nationally representative surveys of the Middle East and North Africa conducted over the past decade we find that socioeconomic status is generally, positively associated with non-violent political behavior of all types. Semi-parametric analysis reveals that political action, in keeping with our signaling framework, exhibits strong non-linear properties: the likelihood of participation in peaceful protests and strikes is highest among the upper-middle class, while support for violence is concentrated among the lower-middle class.
Keywords: D74; N45; N47; 330; political behavior; Arab world; signaling models